Effect of dietary carbohydrate content on blood glucose levels of swimmers during training - Soultanakis, H.; Platanou, T. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. Data, as far as the impact of carbohydrate content of diets on training performance, are limited and conflicting and blood glucose levels during swimming training have never been reported. The purpose of this study was to determine if the type of diet can influence blood glucose levels during a regular swimming training session. Methods. Twelve elite male swimmers with a mean age of 15.7±0.67 years were enrolled for this study. Prior to testing, the swimmers were subjected to: 1) body composition analysis, 2) maximal heart rate determination, and 3) estimation of resting and swimming energy expenditure. Subsequently, swimmers were put on two isocaloric three-day diets, containing either a high percentage of carbohydrate (HCD-65%) or a low percentage of carbohydrate (LCD-35%) before performing the two 110 minutes training sessions (inter-spaced by 6-8 days) at an intensity of 75% of peak heart rates. Blood glucose was collected and analyzed at 0, 20, 60 and 110 minutes of exercise. Results. Blood glucose under both dietary conditions initially dropped and thereafter rose again by the end of the 110 minute training session. The data revealed that blood glucose never dropped to hypoglycemic levels, but showed a different pattern of changes throughout training. Conclusion. The carbohydrate content of the diet followed for a period of three days prior to testing, does not appear to directly affect blood glucose levels throughout a swimming training session lasting over 90 minutes, in elite national level swimmers.